A Transcatheter Closure of Large-Size Patent Ductus Arteriosus with Severe Degree of Pulmonary Hypertension by Different Types of Devices - Mohanad K Shukur Al Ghanimi; Hussein A Alsalkhi; Mohanad Fadhil Alkhafaji (Mashhad University of Medical Sciences, 2023)
Background: Transcatheter closure is the most common treatment for patent ductus arteriosus (PDA); however employing large PDA is difficult because there are few closure devices, and surgical treatment is risky, especially in young infants with low weight and adults with calcified PDA. This study examines transcatheter closure and pulmonary artery (PA) pressure reversibility in large PDA with severe pulmonary hypertension. Methods: A prospective research examined high PA pressure in 34 patients with big PDA and severe pulmonary hypertension (PHT) who were closed with various occludes. Clinical and transthoracic echocardiographic follow-up at 4 weeks, 3 months, 6 months, and 12 months post-closure measured PA pressure and closure effectiveness. Results: In total, 34 big PDAs with significant PHT were transcatheter-closed in 723 individuals. Patients were from a few months old to adults and weighed from 4.25 to 61kg, which were tested by using ADO1, MVSD, AVP2, ASDO, and a stent-closed PDAs. After the intervention, the PA systolic, mean, and diastolic pressures were 36.85±11.12mmHg, 29.24±10.09mmHg, and 23.35±8.82 mmHg, respectively. Moreover, after the intervention, the aortic systolic, mean, and diastolic pressures were 112.38±16.97mmHg, 76.00±9.73mmHg, and 61.88±8.73mmHg, respectively. Two instances showed rebound PA pressure 3 months after effective treatments that did not respond to pulmonary vasodilator therapy. The median size of PDA in 10 cases closed by MVSD was 11.59±3.15mm, and the device size was 16.20±3.46mm; moreover, the defect size in 15 cases closed with ADO I device was 9.19±3.46mm, and the median size of occluder was 11.07±4.06mm. In 4 cases, the median size was 5.15±0.65mm, mostly in infants closed by an AVP2 occluder with a device size of 8.50±1.00mm. Conclusion: Transcatheter closure of large PDA with severe PHT using the off-labeled device is feasible and effective. Meticulous and continuous assessment and evaluation of PHT response for closure is mandatory to confirm longstanding efficacy and safety.